Rise and fall in the Third Reich: Social mobility and Nazi membership - Matthias Blum; Alan De Bromhead (Queen's University Centre for Economic History (QUCEH), 2017)
This paper explores the relationship between Nazi membership and social mobility using a unique and highly detailed dataset of military conscripts and volunteers during the Third Reich. We find that membership of a Nazi organisation is positively related to social mobility when measured by the difference between fathers' and sons' occupations. This relationship is stronger for the more 'elite' NS organisations, the NSDAP and the SS. However, we find that this observed difference in upward mobility is driven by individuals with different characteristics self-selecting into these organisations, rather than from a direct reward to membership. These results are confirmed by a series of robustness tests. In addition, we employ our highly-detailed dataset to explore the determinants of Nazi membership. We find that NS membership is associated with higher socio-economic background and human capital levels.
Keywords: J62; N24; N44; P16; 330; National Socialism; Third Reich; Social Mobility; Nazi Membership; Second World War; Political Economy; Germany; Economic History